Orthodox Christian identity in Western Europe: contesting religious authority - Rimestad, Sebastian (Routledge studies in religion, 2021)
The Orthodox faithful as 'diaspora'? The pastoral discourse -- The territoriality of Orthodox Church structures : the ecclesiological discourse -- Orthodox jurisdictions as organisations : The institutional discourse -- The Christian Church as one : the ecumenical discourse.